Analysis Of Differences In Stock Prices Of Islamic Banks And Conventional Banks During The Covid-19 Pandemic For The Period 2018-2022 - Kholidah, Farah Zulfa; Puspita, Rosana Eri; Ardana, Yudhistira (Universitas Islam Negeri Raden Intan, 2023)
The COVID-19 outbreak has affected PT Perbankan in Indonesia. This study aims to determine the difference in Islamic and Conventional Banks' stock prices before COVID-19 and after COVID-19. The data used in this research is secondary data from quarterly stock price reports listed on the IDX. The results of the differential test using the Paired Sample T-test and Wilcoxon Rank Test show that there are differences in the share prices of Islamic Banks before COVID-19 and after COVID-19, and there are differences in the share prices of Conventional Banks before COVID-19 and after COVID-19. Researchers hope this research can add knowledge and insight for readers, and further researchers can add other factors or variables.